Evaluation on Hydnophytum formicarum Tuber from Setiu Wetland (Malaysia) and Muara Rupit (Indonesia) for Antibacterial and Antioxidant activities, and anti-cancer Potency against MCF-7 and HeLa Cells - Yosie Andriani, Habsah Mohamad, Murni Nur Islamiah Kassim, Nur Diyana Rosnan, Desy Fitrya Syamsumir, Jasnizat Saidin & , Tengku Sifzizul Tengku Muhamma, Hermansyah Amir (Journal of Applied Pharmaceutical Science, 2017)
This current study is to evaluate and compare the antibacterial, antioxidant and anticancer activity of H. formicarum tubers from Setiu Wetland, Terengganu, Malaysia and inland forest of Muara Rupit, Sumatera-Selatan, Indonesia. The tubers were extracted using methanol and then sequentially fractioned using solvent partitioning by n-hexane, dichloromethane, and ethyl acetate. The phytochemical study showed that samples from both places possessed same phytochemicals content that was rich with phenols, tannins, steroids, and glycosides. Extract from Setiu exhibit antibacterial activity against all tested bacteria, while methanol extract from Muara Rupit was only active against Gram positive bacteria. All samples showed high DPPH free radical scavenging activity (IC50 less than 10 µg/ml). Via MTS assay, no cytotoxic activity of all samples was observed against HeLa cells. Only a fraction from Setiu Wetland showed very strong cytotoxic activity against MCF-7 cells (IC50 = 2 µg/ml) and its morphological features stained by Annexin-V/PI and DAPI showed that the cell death was mediated by apoptosis. Results revealed that H. formicarum tuber from Setiu wetland and Muara Rupit showed very good potency as antibacterial and antioxidant agents. The only sample from Setiu wetland has a good potency as anticancer against MCF-7 cells but not against HeLa cells.
Keywords: Hydnophytum formicarum, DPPH, Antibacterial, Apoptosis, MCF-7,HeLa.